2019
DOI: 10.1093/gji/ggz481
|View full text |Cite
|
Sign up to set email alerts
|

The short-term seismicity of the Central Ionian Islands (Greece) studied by means of a clustering model

Abstract: SUMMARY Earthquake clustering in the area of Central Ionian Islands (Greece) is statistically modelled by means of the Epidemic Type Aftershock Sequence (ETAS) branching model, which is the most popular among the short-term earthquake clustering models. It is based upon the assumption that an earthquake is not fully related to any other one in particular, but rather to both all previous events, and the background seismicity. The close temporal proximity of the strong ($M \ge 6.0$) events in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…This study revealed that the joint implementation of physics-based approaches and the statistical ETAS model is beneficial for future OEF systems. Kourouklas et al (2020) Mangira et al (2020), revealing that the employed ETAS clustering model provides reliable forecasts of the aftershock activity for this region.…”
Section: Region Of Studymentioning
confidence: 91%
“…This study revealed that the joint implementation of physics-based approaches and the statistical ETAS model is beneficial for future OEF systems. Kourouklas et al (2020) Mangira et al (2020), revealing that the employed ETAS clustering model provides reliable forecasts of the aftershock activity for this region.…”
Section: Region Of Studymentioning
confidence: 91%
“…The model considers earthquakes as the realization of a Hawkes process, namely as a point with coordinates (x, y, t, m) corresponding to its geographical position (x, y), occurrence time (t) and earthquake magnitude (m). As in previous publications [7,8,23], we neglected depth as a spatial coordinate. We based this decision on the fact that the depths of the crustal earthquakes in our catalog range between 3 and 15 km.…”
Section: Brief Description Of the Earthquake-clustering Modelmentioning
confidence: 99%
“…The maximum magnitude that the simulator generates will also be influenced by the effect of the value of A-R. A wide range of Aσ values are reported, ranging from 0.0012 to 0.6 MPa, obtained from different earthquake sequences (Harris, 1998;Harris and Simpson, 1998). Mangira et al 2020 tested values ranging between 0.04 and 0.09 MPa in the Central Ionian Islands (Greece), with a value equal to Aσ 0.06 MPa found to be the most appropriate. Console et al 2020 used values between 0.01 and 1.0 Mpa concluding Aσ 0.05 MPa for Central Italy.…”
Section: Application Of the Simulator To The Southern Thessaly Fault mentioning
confidence: 99%
“…These improved versions were successfully applied to simulate the seismicity of Calabria (Console et al, 2017;Console et al, 2018b) and Central Apennines (Console et al, 2018a) in Italy. The latest version of the algorithm incorporates the effect of the Rate and State Constitutive law proposed by Dieterich 1994 in the physical processes, leading to a stochastic manner of nucleation with applications in Central Italy (Console et al, 2020) and Greece (Mangira et al, 2020).…”
Section: Introductionmentioning
confidence: 99%